PENGARUH APE BOWLING HURUF HIJAIYYAH TERHADAP KEMAMPUAN MENGENAL HURUF HIJAIYYAH ANAK USIA DINI - Siti Labiba Kusna; Maratus Shalikah (Abata : Jurnal Pendidikan Islam Anak Usia Dini, 2021)
This study aims to determine the effect of the bowling hijaiyyah educational game tool on the ability to recognize hijaiyyah letters for children aged 4-5 years at RA Al-Makmur Mayangrejo, Kalitidu District, Bojonegoro. This research uses quantitative research with an experimental approach. The subjects in this study were all 15 children of group A in RA Al-Makmur. Data was collected by using interview, observation and documentation techniques. The data analysis technique in this study was statistical tests and described the data. The results of research and hypothesis testing have shown that the achievement of children's development in recognizing hijaiyyah letters has increased, so that the hijaiyyah bowling educational game tool has an effect on better cognitive development, namely children are able to recognize hijaiyyah letters. Descriptive analysis obtained from the results of the Wilcoxon sign test can be seen that the Asymp value. Sig. <0.05, so it can be concluded that Ho is rejected and Ha is accepted. So, there is a significant influence on the development of the ability to recognize hijaiyyah letters between before and after the use of the hijaiyyah bowling educational game tool. This increase shows that the bowling hijaiyyah educational game tool affects the ability to recognize hijaiyyah letters for children aged 4-5 years.